Optical Properties of Composites Formed by Transition Metal Macrocyclic Complexes Intercalated in Thiophosphate Layered Phases - Venegas-Yazigi, D; Venegas-Yazigi, D (2012)
Hybrid materials, formed by strong absorbing macrocyclic complexes [Zn 2L]·(NO 3) 2·H 2O or [MnL(H 2O) 2]·NO 3·H 2O (LH 2: macrocyclic ligand obtained from the [2 + 2] condensation of 2-hydroxy-5-methyl-1,3-benzenedicarbaldehyde and 1,2-diaminobenzene) intercalated in MnPS 3 and CdPS 3 layered phases, were obtained by the ion exchange method using the potassium precursor, K 0.4M 0.8PS 3(H 2O) x. As a result of the conventional synthetic method, using stirring at room temperature, the following composites were obtained: [Zn 2L] 0.05K 0.30Mn 0.80PS 3(H 2O) x (1), [Zn 2L] 0.10K 0.20Mn 0.80PS 3(H 2O) x (2), [Zn 2L] 0.05K 0.30Cd 0.80PS 3(H 2O) x (4), [MnL] 0.25K 0.15Mn 0.80PS 3(H 2O) x (6), [MnL] 0.35K 0.05Mn 0.80PS 3(H 2O) x (7) and [MnL] 0.25K 0.15Cd 0.80PS 3(H 2O) x (9). While the microwave assisted method gives: [Zn 2L] 0.05K 0.30Mn 0.80PS 3(H 2O) x (3), [Zn 2L] 0.05K 0.30Cd 0.80PS 3(H 2O) x (5), [MnL] 0.25K 0.15Mn 0.80PS 3(H 2O) x (8) and [MnL] 0.15K 0.25Cd 0.80PS 3(H 2O) x (10). The luminescent properties of the macrocyclic zinc(II) and manganese(III) complexes are not observed in the final composites due to the radiationless decay processes, which are favored by the packing of the macrocyclic species between the layers of the MPS 3 phase. The solid reflectance UV-Vis spectra indicate that the absorption edge of the composites is shifted to lower energies, as compared to the potassium precursor, 2.85 eV for K 0.4Mn 0.8PS 3(H 2O) x and 3.20 eV for K 0.4Cd 0.8PS 3(H 2O) x. The absorption edge varies from 1.85 to 1.70 eV, depending on the stoichiometry of the composite. © 2012 Published by Elsevier Ltd. All rights reserved.